(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In the article, religious views of Muhammad bin Abdulwahhab, who lived on the Arabian Peninsula in the 18th century, are tested on the basis of the Treatise of Kashf al-Shubuhat on religious-textual and rational-logical basis. Resemblances between the views of the author and the teachings of Ibn Taimiyah are considered. Prerequisites and justifications of the Takfiri idea in the teachings of Ibn Abdulwahhab are identified and analyzed. Aggressive methods in carrying his teachings to the reader are concretized. Attempts are made to explain the purpose of this writingthrough the texts of the treatise. It is proved that Ibn Abdulwahhab openly condemned by disbelief or by giving acommunion to the Godall the Muslims who disagree with him, in particular the followers of the Sufism. Not only the condemnation, but he also called his followers to shed their blood. Critical reviews regarding the content and purpose of the treatise texts are based on the principles of Islamic Sharia and the principles set forth by the scholars. It is possible to say that through this article the most dangerous aspectsof the treatise and the teachings of Ibn Abdulwahhab,which are not intelligible for ordinary Muslims, are revealed. Key words: The Prophet, kufr / unbelief, takfir, takfirizm, Islam, sharia, Quran, hadith, iman / faith, kafir / unbeliever, Mohammed bin Adulwahhab, Muslims, Najdi region, exposing of doubts, tauassul, istigasa, giving a partner, intercession.